Puerarin Attenuates High-Glucose and High-Lipid-Induced Inflammatory Injury in H9c2 Cardiomyocytes via CAV3 Protein Upregulation - Tian Y; Zhou C; Bu X; Lv Q; Huang Q (Dove Medical Press, 2023)
YiFu Tian,1 CaiXia Zhou,1 XiaoYang Bu,1 Qian Lv,1 Qin Huang1,2 1Department of Physiology of Basic Medical Sciences, Guangxi Medical University, Nanning, People's Republic of China; 2Department of Key Laboratory of Longevity and Aging-Related Diseases of Chinese Ministry of Education & School of Basic Medical Sciences, Guangxi Medical University, Nanning, People's Republic of ChinaCorrespondence: Qin Huang, Department of Physiology, Guangxi Medical University, Building 102, 22 Shuangyong Road, Nanning, Guangxi, 530021, People's Republic of China, Email hqgxmu@163.comBackground: Inflammation plays a crucial role in the development of diabetic cardiomyopathy (DCM), including inflammation caused by high-glucose and high-lipid (HGHL). Targeting inflammation may provide a useful strategy for preventing and treating DCM. Puerarin has been shown to reduce the inflammation, apoptosis and hypertrophy of cardiomyocytes induced by HGHL, in which this study aims to investigate the underlying mechanisms.Methods: H9c2 cardiomyocytes cultured with HGHL were used to establish a cell model of DCM. Puerarin was then placed to these cells for 24 hours. The effects of HGHL and puerarin on cell viability and apoptosis were investigated by the Cell Proliferation, Toxicity Assay Kit (CCK-8) and flow cytometry. Morphological changes of cardiomyocytes was observed by HE staining. CAV3 proteins in H9c2 cardiomyocytes were altered by transient transfection of CAV3 siRNA. IL-6 was detected by ELISA. The Western blot was performed to determine the CAV3, Bcl-2, Bax, pro-Caspase-3, cleaved-Caspase-3, NF-κB (p65) and p38MAPK proteins.Results: Puerarin treatment reversed the cells viability, hypertrophy in morphology, inflammation (showed by p-p38 and p-p65 and IL-6) and apoptosis-related damage (showed by cleaved-Caspase-3/pro-Caspase-3/Bax, Bcl-2 and flow cytometry) of the H9c2 cardiomyocyte caused by HGHL. Puerarin treatment also restored the decrease of CAV3 proteins of the H9c2 cardiomyocyte caused by HGHL. When silenced the expression of CAV3 proteins with SiRNA, puerarin failed to decreased p-p38 and p-p65 and IL-6, and could not reversed cell viability and morphological damage. In contrast to the simple CAV3 silenced group, the CAV3 silenced with NF-κB pathway or p38MAPK pathway inhibitors, significantly downregulated the p-p38, p-p65 and IL-6.Conclusion: Puerarin upregulated CAV3 protein expression in H9c2 cardiomyocytes and inhibited the NF-κB and p38MAPK pathways, thereby reducing HGHL-induced inflammation and may related to the apoptosis and hypertrophy of cardiomyocytes.Keywords: puerarin, cardiomyocyte, inflammation, caveolin-3, siRNA, NF-κB, p38MAPK